A proof-of-concept study showing antibiotics to be more effective in irritable bowel syndrome with than without small-intestinal bacterial overgrowth: a randomized, double-blind, placebo-controlled trial. Issue 3 (March 2016) - Ghoshal, Uday C.; Srivastava, Deepakshi; Misra, Asha; Ghoshal, Ujjala
Abstract : Background: Antibiotics relieve symptoms in half of the unselected patients with irritable bowel syndrome (IBS); however, their efficacy if selected according to small-intestinal bacterial overgrowth (SIBO) is unknown. Aims: The aim of this study was to evaluate (a) symptom resolution among IBS patients with or without SIBO on norfloxacin treatment, and (b) its efficacy in obtaining negative SIBO test results as compared with placebo. Method: Eighty IBS patients (Rome III) were evaluated for SIBO by gut aspirate culture. Patients with (≥10 5 CFU/ml) and those without SIBO were separately randomized (computer-generated stratified) to 800 mg/day norfloxacin for 10 days or placebo. Global symptom score (blindly), Rome III criteria, aspirate culture, and glucose hydrogen breath test (GHBT) were assessed before and 1 month after treatment, and patients were followed up for 6 months. Results: Although norfloxacin was more effective at reducing the symptom score at 1 month among patients with compared with those without SIBO [15/80, 19% on culture, four on GHBT too; 6.5 (2–13) vs. 2 (0–10), P =0.01; 8.5 (2–16) vs. 5 (0–12), P <0.001] but not placebo, the scores were comparable at 6 months [3 (1–10) vs. 9 (5–19), P =NS]. Symptoms more often resolved to turn Rome III negative in SIBO patients treated with norfloxacin compared with placebo at 1 month (7/8, 87.5 vs. 0/7, P =0.004); of the other 65 patients, 8/32 (25%) treated with norfloxacin but none of the 33 treated with placebo turned Rome III negative. Patients without SIBO and a colony count of 10 3 –10 5 CFU/ml responded more than those with a colony count less than 10 3 CFU/ml. Overall, 15/40 (37.5%) patients responded to norfloxacin. At 6 months, 2/8 (25%) with and 5/32 (15.6%) without SIBO remained Rome III negative following norfloxacin. All 4/8 consenting patients treated with norfloxacin became SIBO negative (two each by culture+GHBT and GHBT alone), but 0/7 patients treated with placebo became SIBO negative. Conclusion: Norfloxacin is superior to placebo in relieving symptoms of SIBO-associated IBS.